Pengaruh dosis pemupukan P dan konsentrasi paclobutrazol terhadap pertumbuhan dan produksi kedelai edamame (Glycine max (L.) Merrill) - Sarah Zulfaniah; Adriani Darmawati; Syaiful Anwar (Department of Biology, Faculty of Sciences and Mathematics, Universitas Diponegoro, 2020)
This research aimed to identify the effect of P fertilization dosage and paclobutrazol concentration on growth and yield of edamame (Glycine max (L.) Merrill). The research used factorials experiment 3x4 with Randomized Complete Block Design (RCBD) consisting of 3 replications. The first treatment was P fertilization dosage such as S1 : SP36 0 kg/ha, S2 : SP36 100 kg/ha, and S3 : SP36 200 kg/ha. The second treatment was paclobutrazol concentration such as P0 : 0 ppm, P1 :100 ppm, P2 : 200 ppm and P3 : 300 ppm. The observed parameters were plant height, leaves total, pods total per plant, seeds total per plant, and 100 seeds weight. The results showed that the treatment of P fertilization dosage had no significant effect on all observed parameters. The treatment of paclobutrazol concentration had a significant effect on plant height, leaves total, pods total per plant, seeds total per parameter, and 100 seeds weight. Optimum paclobutrazol concentration on plant height, leaves total, and 100 seeds weight parameters was 0 ppm. Paclobutrazol 100 ppm produced the highest response to pods total per plant and seeds total per plant.